Analysis of the Proper Motion of Sunspots before the Flare Onset on NOAA 0375 and NOAA 9715 - Clara Yono Yatini; Rasdewita Kesumaningrum; Santi Sulistiani (Institut Teknologi Bandung, 2007)
We have examined the movements of individual sunspots within two sunspot groups, NOAA 0375 in association with M7.3 flare appeared on 12 June 2003 and NOAA 9715 associated with M1.3 flare on 2 December 2001. For this purpose we measured the distance of two bipolar spots directly related to the flares with respect to a reference spot in the active region during the period before flare activity and estimated the average velocity of their movements. The main result is that the spots related with flares had average velocity greater than the flare-unrelated spots.